The role of myocardial wall thickness in atrial arrhythmogenesis - Whitaker, John; Rajani, Ronak; Chubb, Henry; Gabrawi, Mark; Varela, Marta; Wright, Matthew; Niederer, Steven; O'Neill, Mark D. (Europace (London, England), 2016)
Changes in the structure and electrical behaviour of the left atrium are known to occur with conditions that predispose to atrial fibrillation (AF) and in response to prolonged periods of AF. We review the evidence that changes in myocardial thickness in the left atrium are an important part of this pathological remodelling process. Autopsy studies have demonstrated changes in the thickness of the atrial wall between patients with different clinical histories. Comparison of the reported tissue dimensions from pathological studies provides an indication of normal ranges for atrial wall thickness. Imaging studies, most commonly done using cardiac computed tomography, have demonstrated that these changes may be identified non-invasively. Experimental evidence using isolated tissue preparations, animal models of AF, and computer simulations proves that the three-dimensional tissue structure will be an important determinant of the electrical behaviour of atrial tissue. Accurately identifying the thickness of the atrial may have an important role in the non-invasive assessment of atrial structure. In combination with atrial tissue characterization, a comprehensive assessment of the atrial dimensions may allow prediction of atrial electrophysiological behaviour and in the future, guide radiofrequency delivery in regions based on their tissue thickness.